PENYIDIKAN POLRI TERHADAP TINDAK PIDANA KORUPSI DI DIREKTORAT RESERSE KRIMINAL KHUSUS POLDA BALI - T. Widodo Rahino (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2018)
This study used qualitative research methods to find the facts straight spaciousness to dig and explore the factors inhibiting what makes Directorate of Special Crime Investigation Bali Regional Police are not optimal in carrying out duties in handling the problem of corruption in Indonesia. The findings of the study authors to submit a brief that the Directorate of Special Crime Investigation Bali Regional Police is not optimal in the performance of its duties in the handling of corruption. Many of the obstacles faced by the Directorate of Special Crime Investigation Bali Regional Police & Police like in terms of personnel, educational background, lack of technical instructions in the investigation regarding the handling of the Criminal Investigation Corruption, inadequate infrastructure, which is still very limited budget, going back and forth frequently the case, still merged the investigation at the Directorate of Special Crime Investigation Bali Regional Police Criminal Investigation Police makes no maximum results in performance of duties by personnel of Directorate of Special Crime Investigation Bali Regional Police. So the conclusion of this research is the Directorate of Special Crime Investigation Bali Regional Police is not optimal in performing law enforcement duties of corruption and other organizational structure recommendation two researchers present the comparison with the Attorney (Assistant Attorney General for Specific Criminal Crime Case) and its Corruption Eradication Commission and other supporting data to prove that the, Directorate of Special Crime Investigation Bali Regional Police in the hope of renewal and improvement of the organizational.